A fast and simple method for detecting and quantifying donor-derived cell-free DNA in sera of solid organ transplant recipients as a biomarker for graft function - Adamek, Martina Maria; Opelz, Gerhard; Klein, Katrin; Morath, Christian; Tran, Thuong Hien (Clinical chemistry and laboratory medicine, 2016)
Background: Timely detection of graft rejection is an important issue in the follow-up care after solid organ transplantation. Until now, biopsy has been considered the “gold standard” in the diagnosis of graft rejection. However, non-invasive tests such as monitoring the levels of cell-free DNA (cfDNA) as a sensitive biomarker for graft integrity have attracted increasing interest. The rationale of this approach is that a rejected organ will lead to a significant release of donor-derived cfDNA, which can be detected in the serum of the transplant recipient.
Gesehen am 20.11.2018
Online erschienen: 17.11.2015